2001
DOI: 10.1200/jco.2001.19.2.480
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Replacement Therapy in Children With Medulloblastoma: Use and Effect on Tumor Control

Abstract: This large retrospective review demonstrates that GHRT is underutilized in survivors of medulloblastoma and is used relatively late in the course of the illness. GHRT is not associated with an increased likelihood of disease relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
10

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 17 publications
3
47
0
10
Order By: Relevance
“…Additional characteristics of the included studies are shown in Table 1. As shown in table, seven of the selected studies obtained seven or more scores, which indicated that the study quality was relatively higher [5][6][7][14][15][16][17][18][19][20][21][22]; whereas, other studies with relatively lesser scores were considered of lower quality [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Additional characteristics of the included studies are shown in Table 1. As shown in table, seven of the selected studies obtained seven or more scores, which indicated that the study quality was relatively higher [5][6][7][14][15][16][17][18][19][20][21][22]; whereas, other studies with relatively lesser scores were considered of lower quality [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…12 However, the results of most studies suggest that GHT is not associated with an increased likelihood of disease relapse. 13 There is no report of OS developing following GHT, 14 however, two-thirds and one-half of Harper et al's 6 and our patients respectively received GHT when OS was identified. Nevertheless, this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 98%
“…Há controvérsias na literatura quanto à indicação da reposição de GH em pacientes que desenvolveram déficit deste hormônio após radiação do crânio para tratamento oncológico na infâncial 11,12 . O GH possui ação mitogênica, podendo estimular células neoplá-sicas residuais e promover a recorrência do tumor 11 .…”
Section: Discussionunclassified
“…Os questionamentos quanto aos efeitos do tratamento com GH no controle do tumor a longo prazo foram contestados recentemente por Packer et al 12 em análise retrospectiva de 545 crianças tratadas com GH após radioterapia por meduloblastoma. Estes autores verificaram que o tratamento com GH não teve efeito sobre a evolução do tumor e ponderaram que a reposição do GH tem sido pouco utilizada e indicada relativamente tarde na evolução do déficit deste hormônio 12 .…”
Section: Discussionunclassified
See 1 more Smart Citation